2016
DOI: 10.1111/pere.12155
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of emotional support in dating relationships: Relational turbulence or sentiment override?

Abstract: This study tests the relational turbulence model by considering how qualities of dating relationships may polarize positive evaluations of partner supportiveness and emotional improvement following an interaction about a stressful experience. Sentiment override, which is the tendency for negative relationship qualities to attenuate positive evaluations of a partner, was evaluated as a competing hypothesis. Using a laboratory-based observation method, participants completed stressful activities and talked with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 87 publications
(156 reference statements)
3
12
0
1
Order By: Relevance
“…Relational turbulence uniquely indexes the overall sense of chaos in the relationship. Following empirical evidence that relational turbulence exerts a distinct influence on reactions to particular events, above and beyond the effect of relational satisfaction (McLaren & Solomon, ; Solomon & Priem, in press), we position it as a separate substantive global quality of romantic relationships. Our reasoning is reflected in a fifth axiom and proposition:
A5: Experiences of specific episodes characterized by biased cognitive appraisals, strong emotions, and polarized communication coalesce into a sense of chaos within the relationship. P5: Through their effect on perceptions of chaos within the relationship, experiences of specific episodes characterized by biased cognitive appraisals, strong emotions, and polarized communication cause global evaluations of the relationship as turbulent.
…”
Section: Relational Turbulencementioning
confidence: 99%
“…Relational turbulence uniquely indexes the overall sense of chaos in the relationship. Following empirical evidence that relational turbulence exerts a distinct influence on reactions to particular events, above and beyond the effect of relational satisfaction (McLaren & Solomon, ; Solomon & Priem, in press), we position it as a separate substantive global quality of romantic relationships. Our reasoning is reflected in a fifth axiom and proposition:
A5: Experiences of specific episodes characterized by biased cognitive appraisals, strong emotions, and polarized communication coalesce into a sense of chaos within the relationship. P5: Through their effect on perceptions of chaos within the relationship, experiences of specific episodes characterized by biased cognitive appraisals, strong emotions, and polarized communication cause global evaluations of the relationship as turbulent.
…”
Section: Relational Turbulencementioning
confidence: 99%
“…That is, do perceptions of turmoil in the relationship account for unique variance beyond the variance accounted for by relationship satisfaction? Research indicates that relationship satisfaction colors overall relationship perceptions such that people who are satisfied perceive their relationships to be more positive, while people who are dissatisfied have more negative views of their relationships, a process known as sentiment override (Solomon & Priem, 2016;Weiss, 1980). Research has shown that, not surprisingly, relational turbulence and satisfaction are negatively correlated (McLaren & Solomon, 2014;Solomon & Priem, 2016;Theiss & Knobloch, 2011).…”
Section: The Present Studymentioning
confidence: 99%
“…Research indicates that relationship satisfaction colors overall relationship perceptions such that people who are satisfied perceive their relationships to be more positive, while people who are dissatisfied have more negative views of their relationships, a process known as sentiment override (Solomon & Priem, 2016;Weiss, 1980). Research has shown that, not surprisingly, relational turbulence and satisfaction are negatively correlated (McLaren & Solomon, 2014;Solomon & Priem, 2016;Theiss & Knobloch, 2011). However, even when controlling for relationship satisfaction, relational turbulence elements still explained significant variance in couple's relationship maintenance behavior (Knobloch & Theiss, 2011), level of emotional support (Solomon & Priem, 2016), and experiences of hurt (McLaren & Solomon, 2014).…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Weiss, ). Although a handful of studies have shown that patterns consistent with the relational turbulence model are robust after covarying relationship satisfaction (e.g., Solomon & Priem, ; Theiss & Knobloch, ), a more complete evaluation of this issue is warranted.…”
Section: Constructs In Relational Turbulence Theorymentioning
confidence: 99%